T265. Fluctuations in craving and mood state bias subjective valuation in addiction (2018)
Background How craving and mood states (e.g., stress, boredom) bias behavior toward rewarding but less adaptive alternatives and away from an individual’s health goals is poorly understood, yet play a critical role in addiction and eating disorders. Here we test the hypothesis that underlying this bias is a state-dependent increase in the subjective value of these rewarding but less-adaptive choice alternatives. Methods 27 treatment-seeking opioid users completed a decision-making task that probed their momentary willingness-to-pay for a range of real opioid use–related and –unrelated goods, a quantitative measure of their value. These goods were identified as most (least) related to an individual subject's use. To capture how dynamics in spontaneous opioid craving and mood affect subjective valuation, patients completed the task over 2 days while continuously reporting their current opioid craving, stress level, boredom, and happiness. Skin conductance and facial EMG were measured concurrently as indices of arousal and valence, respectively. Results Subjects were willing to pay more specifically for personalized opioid-related goods when experiencing higher craving, stress, and boredom and lower happiness (subjective state level X opioid-relatedness: P<0.016). Despite mild correlation across subjective states (R=0.14–0.51), the effects of each on valuation were largely independent, particularly of craving and stress. Analysis of physiological data is ongoing, but we hypothesize these data will serve as auxiliary, objective measures of how subjective states bias valuation. Conclusions These data suggest craving and stress both enhance the value of less-adaptive choice alternatives when these are immediately rewarding, potentially reflecting a compensatory mechanism aimed at buffering these states.